Gagasan Moderasi Beragama: Menguak Pluralisme dalam Pembaharuan Islam Nurcholish Madjid - Dias, Hendri Pani; Julhadi, Julhadi; Hanafi, Abdul Halim (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
This research wants to reveal Nurkholish Madjid's ideas regarding Islamic reform within the framework of religious moderation. It is important for us to highlight this idea here because in the modern era, violence has spread due to excessive fanaticism. The reason is that there are certain groups who are not responsible in their name as Muslims but act according to their own wishes. Of course, there must be an idea of religious moderation for those who always commit acts of violence in the name of religion. Cak Nur is working hard to uncover the true veil of Islam through the lens of Islamic universalism. Monotheism is the initial basis for Muslims in re-establishing moderate concepts in religion. By using a library research approach, this research wants to reveal Cak Nur's ideas in the frame of religious moderation. Because the religious moderation developed by Cak Nur is moderation that prioritizes humanity and justice which are no longer negotiable. This vision of humanity and justice has been implemented in the true teachings of Islam. If today there are Muslims who cannot put forward a vision of humanity and justice, it means they have not been able to understand Islam universally and deeply. The Islam that we understand is Islam that always prioritizes a vision of complete humanity.